A New Duplex Recombinase Polymerase Amplification (D-RPA) Method for the Simultaneous and Rapid Detection of Shigella and Bacillus cereus in Food - Shuna Xiang; Hanyue Zhang; Xiaoyan Cha; Yingting Lin; Ying Shang (Foods, 2023)
Shigella and Bacillus cereus are two common foodborne pathogens that cause intestinal diseases and seriously affect human life and health. Traditional microbiological culture methods are time-consuming and laborious, and polymerase chain reaction (PCR)-based methods rely on expensive thermal cyclers and lengthy reaction times. In this study, on the basis of the specific gene ipaH7 of Shigella and the virulence gene nheABC of B. cereus, a duplex detection system was established for the first time by using the recombinase polymerase amplification technique (D-RPA). After optimization, D-RPA could be effectively amplified at 42 °C for 25 min with excellent specificity, and the detection limits of D-RPA for Shigella and B. cereus in artificially contaminated samples were 2.7 × 101 and 5.2 × 102 CFU/mL, respectively. This study provides a certain research basis for multiple detection with RPA, an isothermal amplification technology. Furthermore, it lays a good foundation for high-throughput rapid detection of foodborne pathogens.